The criticism of Kant’s pure reason as immanent criticism - Caviglia, Alessandro (2017)
The current work expounds how the Critique of Pure Reason not only incorporates a criticalMetaphysics, but can be useful as a basis for developing the critical theory of society, asthe representatives of the Frankfurt School do. This is possible, illuminating the fact thatreason is not something outside the world but is found in people who are in a specific socialworld. In this way, the reason is the basis that enables the exchange of reasons amongpeople, in order to develop an immanent critique of society.